2023
DOI: 10.3390/su15032587
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Estimation of Soil Organic Carbon Content Based on Continuous Wavelet Transform and Successive Projection Algorithm in Arid Area of Xinjiang, China

Abstract: Soil organic carbon (SOC), an important indicator to evaluate soil fertility, is essential in agricultural production. The traditional methods of measuring SOC are time-consuming and expensive, and it is difficult for these methods to achieve large area measurements in a short time. Hyperspectral technology has obvious advantages in soil information analysis because of its high efficiency, convenience and non-polluting characteristics, which provides a new way to achieve large-scale and rapid SOC monitoring. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In our study of the feature selection process for soil hyperspectral data, we found that the SPA effectively retained spectral feature information. This finding is consistent with previous studies on SOC estimation conducted by Peng et al [18] in Jiangsu and Hubei province, and Huang et al [33] in the Arid Area of Xinjiang. However, a study conducted in Romania found that mutual information is the optimal algorithm for screening soil spectral features [23].…”
Section: Comparison Of Different Algorithmssupporting
confidence: 93%
“…In our study of the feature selection process for soil hyperspectral data, we found that the SPA effectively retained spectral feature information. This finding is consistent with previous studies on SOC estimation conducted by Peng et al [18] in Jiangsu and Hubei province, and Huang et al [33] in the Arid Area of Xinjiang. However, a study conducted in Romania found that mutual information is the optimal algorithm for screening soil spectral features [23].…”
Section: Comparison Of Different Algorithmssupporting
confidence: 93%
“…Oases are non-zonal landscapes formed under dry climatic conditions with a desert substrate, lakes, and oasis land as main patches, supporting high agricultural productivity. Physicochemical processes in lakeside oasis soil environments are controlled by soil organic carbon (SOC), which is also a key determinant of soil fertility and agricultural potential [1,2]. Therefore, the rapid monitoring of the SOC content could provide a scientific basis for the rational development of land resources and precision agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous wavelet transformation (CWT) has an excellent capability for time-frequency analysis, and it has potential as an effective method for enhancing the spectral response, characterizing local features of the spectral signal, and more effectively extracting information of small spectral features in soil [12]. It has also been proven to be effective as a pre-processing method [2,13]. The accuracy of SOC content estimation is affected by various factors, such as outdoor temperature, vegetation cover, soil surface roughness, wind, and the redundancy of the full-band spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the moment, differential transform and wavelet transform are the major preprocessing techniques used for SOM spectral reflectance data. In their study, Huang et al [5] focused on arid soil data and utilized a continuous wavelet transform with different scales to eliminate noise in the data. They combined it with a continuous projection algorithm for feature band extraction and used multiple regression methods to construct an inversion model of the soil organic carbon content.…”
Section: Introductionmentioning
confidence: 99%